Implementasi pengelolaan keuangan pada sekolah multijenjang: studi kasus di sekolah indonesia kuala lumpur - Maulidia, Dinda Nur (Maliki Interdisciplinary Journal, 2026)
This study aims to know implementation of financial management at Sekolah Indonesia Kuala Lumpur (SIKL) as a multilevel school that includes PAUD, TK, SD, SMP, and SMA levels. Through a qualitative approach with an in-depth interview method with the school treasurer, this research reveals the strategy of planning, distributing, and monitoring funds from various sources, namely the state budget (Adikbud), Indonesian Schools Abroad (SILN) funds, and School Activity Support Funds (DDKS) with a reimbursement-based management system and proposal submission. Interviews showed that although there is no separation of fund allocations by education level, the management process is integrated with multiple levels of supervision. The main challenges in financial management are the timeliness of reporting and budget limitations due to funding cuts. Technology plays a limited role, with the use of simple applications such as Excel and digital filing. Recommendations from the treasurer emphasize the importance of individual responsibility, cross-divisional synchronization and increased transparency, especially towards teachers and guardians. The findings are expected to inform the evaluation and development of financial management systems in other multilevel schools